ANALISIS VEGETASI DAN PENENTUAN DOMINANSI GULMA PADA PERTANAMAN JAGUNG DI BEBERAPA KETINGGIAN TEMPAT - Gayuh Prasetyo Budi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2018)
This research was conducted to study weed species and weed dominance on maize crop at several altitutes in Kembaran districts (0-250 m alt) and Sumbang Districs (250-500 m alt), Banyumas regency. The research was arranged in a survey and weed vegetation analysis on maize crop at two different locations determined. There are 6 locations of maize crops every altitutes level (each 20mx20m). Every fields determined 10 samples plot (each 1mx1m). The results showed that weed dominance on maize crop (0-250 m alt) are Cynodon dactylon (SDR : 12,39), Eclipta prostrata (SDR : 11,09), Digitaria sanguinalis (SDR : 9,76), Leptochloa chinensis (SDR : 9,53) dan Cyperus rotundus (SDR : 8,82). Weed dominance on maize crop (250-500 m alt) are Eclipta prostrata (SDR : 13,78), Cynodon dactylon (SDR : 12,81), Leptochloa chinensis (SDR : 12,29), Cyperus rotundus (SDR : 11,47) dan Digitaria sanguinalis (SDR : 10,46).